Texts with Various Levels of Hardness, Reading Comprehension and Reading Motivation: I+1 Versus I-1 - Namaziandost, Ehsan; Rahimi Esfahani, Fariba; Nasri, Mehdi (ELT Forum: Journal of English Language Teaching, 2019)
Considering the vital role of comprehensible input, this study attempted to compare the effects of input with various difficulty levels on Iranian EFL learners’ reading comprehension and reading motivation. To fulfil this objective, 54 Iranian pre-intermediate EFL learners were selected from two intact classes (n = 27 each). The selected participants were randomly assigned to two equal groups, namely “i+1” (n=27) and “i-1” group (n=27). Then, the groups were pretested by a researcher-made reading comprehension test. After carrying out the pre-test, the treatment (i.e., extensive reading at different levels of difficulty) was practiced on the both groups. The participants in “i+1” group received reading passages beyond the current level, on the other hand, the “i-1” group received those reading passages which were below their current level. After the instruction ended, a modified version of pre-test was conducted as posttest to determine the impacts of the treatment on the students’ reading comprehension. The obtained results indicated that there was a significant difference between the post-tests of “i+1” and “i-1” groups. The findings showed that the “i+1” group significantly outperformed the “i-1” group (p < .05) on the post-test. Moreover, the findings indicated that “i+1” group’s motivation increased after the treatment. The implications of the study suggest that interactive type of input is beneficial to develop students’ language skills. Keywords: Comprehensible Input; Extensive reading; Foreign language reading motivation; Input; Reading comprehension; Text difficulty level